KARAKTERISTIK SENSORIS DAN SIFAT FISIKO KIMIA KOPI ARABIKA SIDIKALANG DARI VARIASI PROSES PASCAPANEN YANG BERBEDA - Budi Mulyara; Ika Ucha Pradifta Rangkuti; Arfan Kirana Siregar (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Indonesia is a large world coffee producer, which is currently followed by the proliferation of coffee shops that provide specialty coffee. Arabica coffee is a type of coffee that is considered to have the better taste among other types of coffee. Sidikalang is one of the coffee producing areas in North Sumatra but has not been fully explored. Traditional processes are still widely used, even though the standard post-harvest process for Arabica coffee is divided into two, namely the wet process and the dry process. This research aims to analyze and compare the sensory and physicochemical characteristics of traditional processing with standard processing of Arabica coffee, especially Sidikalang Arabica coffee. The physical quality of the traditional process and natural process is in category 2 while the wet process is in category 1 based on the Indonesian National Standards (SNI) 2008 for coffee beans. The caffeine content of all treatments meets the 2004 SNI standard of below 2%. Carbohydrate levels are relatively low, with an average value below 30%. The Percent Extraction (PE) in espresso meets standard values ranging from 18% to 22%. Wet processes tend to be very popular in terms of fragrance, acidity, bitterness, and body, while natural processes and traditional processes are dominant in terms of fragrance.